(untitled) (Acta Scientiarum. Biological Sciences, 2026)
The current study aimed to collect stool samples from patients visiting Sharqat General Hospital and primary healthcare centers in Salah ad-Din Governorate to diagnose some the species of Entamoeba parasite using the molecular PCR technique, and by designing specialized primers to detect parasite DNA. The study spanned a period of time extending from the beginning of November 2023 to the end of March 2024. Stool samples were collected from individuals infected with amoebic parasites after they were clinically diagnosed by doctors based on their symptoms. Patient data was obtained and classified to determine if they were infected with parasites. Microscopic analyses were carried out on the stool in order to determine if individuals were infected with Entamoeba. PCR was utilized in molecular studies and every case identified using microscopy was confirmed by the molecular assay. We conclude the PCR technique is very accurate in diagnosis species of organisms, and this was observed through what was obtained from the current study.